Ocorrência de Scaptocoris castanea, perty 1830 em pastagens cultivadas no Brasil - Costa, Ciniro [UNESP]; Forti, L. C. (Empresa Brasileira de Pesquisa Agropecuária (EMBRAPA), 1993)
The brown bug (Scaptocoris castanea, Perty 1830) is an insect of underground habits, which continuously suctions the juice through the roots leads the plants to emaciate, dry and die. It has not yet been described as pest in cultivated pastures in Brazil. Its occurrence has been observed in cultivated pastures of Cynodon dactylon cv. Coast cross and Brachiaria decumbens cv Brasilik and IPEAN in red-yellow podzolic soil originally covered by savannah vegetation, in Botucatu County, state of São Paulo.

O percevejo-castanho (Scaptocoris castanea, Perty 1830) é um inseto de hábitos subterrâneos que, pela sucção contínua da seiva através das raízes, leva as plantas ao definhamento, secagem e morte. O inseto até então não constava como praga das pastagens cultivadas no Brasil. Sua ocorrência foi observada em pastagens cultivadas de Cynodon dactylon cv. Coast cross e Brachiaria decumbens cv. Brasilik e IPEAN, em solo Podzólico Vermelho-Amarelo distrófico, originalmente coberto por vegetação de cerrado, no município de Botucatu, Estado de São Paulo.
Occurrence of Scaptocoris-castanea, perty, 1830 in cultivated pastures in Brazil